Impact of the Lacson flyover on the traffic along its adjacent road network - Aguilar, Phillip Eleazar S.; Dela Peña, Justin Royce P.; Peralta, Mathew Harvey T. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Arsenio H. Lacson Avenue, a segment of the C-2 arterial, is one of the busiest roads in the City of Manila. To address the high levels of traffic congestion on the area and its adjacent intersecting roads, DPWH proposed the construction of a flyover along Lacson Avenue. The analysis of the impacts of this project is necessary to determine its effectiveness and to confirm if the corresponding changes in traffic conditions are substantial enough considering different scenarios. For this study, the obtained data were simulated using VISSIM to analyze the performance per intersection using average travel speed, average travel time, average delay time and average queue length as main parameters. The traffic and geometric data from the base year (2016) and projected data, for the year of start of operation (2019) and end of design life (2039), with and without flyover cases, were subjected for further evaluation and traffic impact analysis. After analysis and evaluation, the results show that the flyover has significant effects on the road network. The analysis of the 2019 traffic data with the proposed flyover shows that the average delay decreased by 11.04%, the average speed increased by 25.17% and the average travel time reduced by 1.99% for the whole network, decreased by 60% for vehicles using the flyover and increased by 5% for vehicles not using the flyover. Moreover, as the flyover is constructed, other parameters such as average queue length and intersection LOS have shown positive effects
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Traffic flow; Elevated highways